2023
DOI: 10.3390/ijms24087122
|View full text |Cite
|
Sign up to set email alerts
|

From Transgenesis to Genome Editing in Crop Improvement: Applications, Marketing, and Legal Issues

Abstract: The biotechnological approaches of transgenesis and the more recent eco-friendly new breeding techniques (NBTs), in particular, genome editing, offer useful strategies for genetic improvement of crops, and therefore, recently, they have been receiving increasingly more attention. The number of traits improved through transgenesis and genome editing technologies is growing, ranging from resistance to herbicides and insects to traits capable of coping with human population growth and climate change, such as nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 126 publications
0
2
0
Order By: Relevance
“…Unlike the conventional breeding method, CRISPR-edited gene is time efficient and stable, as there is no distinguishable difference between the variants generated from genome editing and those obtained from naturally occurring variations ( Marone, Mastrangelo & Borrelli, 2023 ; Anders, Hoengenaert & Boerjan, 2023 ). It was also more readily accepted in the market for commerce ( Brandt & Barrangou, 2019 ).…”
Section: Impact Of Crispr-cas In Managing the Environmental Stress On...mentioning
confidence: 99%
“…Unlike the conventional breeding method, CRISPR-edited gene is time efficient and stable, as there is no distinguishable difference between the variants generated from genome editing and those obtained from naturally occurring variations ( Marone, Mastrangelo & Borrelli, 2023 ; Anders, Hoengenaert & Boerjan, 2023 ). It was also more readily accepted in the market for commerce ( Brandt & Barrangou, 2019 ).…”
Section: Impact Of Crispr-cas In Managing the Environmental Stress On...mentioning
confidence: 99%
“…The utilization of biotechnology is of paramount importance in managing insect pests to safeguard crops and enhance yields. This encompasses a broad spectrum of activities, ranging from the development of pest-resistant breeds to the genetic modification of novel genes through introgression [41]. The developing stage of utilizing genome-editing methodologies for insect-resistant plants is currently underway.…”
Section: Potentiality Of Revolutionizing Pest Management Using Crispr...mentioning
confidence: 99%
“…Several reports have shown that transformation efficiency in melon is notably low [ 14 , 15 ]. This limitation hinders the application of transgenesis and genome editing for functional genomics studies [ 16 , 17 ]. Different factors affect the Agrobacterium -mediated transformation efficiency, particularly those related to the inoculation and co-cultivation medium conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Melon organogenesis and embryogenesis are typically performed using leaf and cotyledon explants. However, several studies have utilized cotyledonary explants for direct shoot organogenesis [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Regeneration of melon plants from cotyledonary explants is more efficient than leaf explants, but it leads to a higher polyploidy level in the regenerated plants [ 20 ].…”
Section: Introductionmentioning
confidence: 99%